Implementación de un manual de calidad para la mejora de la productividad de la avícola san Vicente del cantón Pujilí, provincia de Cotopaxi, periodo 2014 - Cajamarca Suárez, Marcelo Fabián (2015)
This study refers to the development of a quality manual for improving the productivity at „San Vicente‟ poultry farm. It exposed a lack of documented processes that enable a management system adjusted to the poultry business. Therefore, it is important to implement a work guide which allows resolving productivity problems in the company. Some disagreements were shown in the work system and it was necessary to find consistent solutions which were processed and analyzed carefully. In addition, the best methods and procedures were implemented in order to improve the deficiencies in poultry production. On the other hand, the work guide was used in different levels within the organization and a quality system based on standard norms served to conclude the operations within the poultry farm. Finally, a well-documented plan in the correct execution of processes helped prevent the impact of hazards which affect the efficient production of fattening poultry.